Exposing Gaps in/Between Discourses of Linguistic Deficits. Issue 1 (2nd January 2017) - Johnson, Eric J.; Avineri, Netta; Johnson, David Cassels
ABSTRACT: Hart and Risley's (1995) concept of a "word gap" (aka "language gap") is widely used to describe inferior cognitive development and lower academic achievement as by-products of the language patterns of families from economically disadvantaged backgrounds. In recent decades, this line of deficit research has proliferated and caused a surge in public exposure in the media and political realms. In this discussion, we employ critical discourse analysis to illuminate intertextual links across three essential domains of "language gap" discourse: (a) academic research literature, (b) public news media, and (c) institutional narratives. The data are analyzed in terms of interdiscursive connections within and between research articles; news and magazine stories; and institutional documents from academic, political, and philanthropic organizations. Here, we demonstrate how discourses that are generated within a socially insulated "language gap" research paradigm propagate a deficit orientation of linguistic minority communities, problematically validate behavior intervention programs among particular socioeconomic groups, and reify linguistic and cultural misperceptions of traditionally marginalized groups.